Multilateral Development Bank Ratings and Preferred Creditor Status - William Perraudin; Andrew Powell; Peng Yang (Inter-American Development Bank (IDB), 2016)
This paper analyzes influences on the credit standing of Multilateral Development Banks (MDBs), specifically the quality, diversification and single name concentration of their portfolios, and on the market practice known as Preferred Creditor Status (PCS), whereby sovereigns that default on other debt rarely fail to meet their obligations to MDBs. The paper examines how rating agencies assess MDB ratings, focusing in particular on how Standard & Poor's assesses capital as part of its MDB rating process. The results are compared with those implied by an industry-standard, ratings-based Credit Risk Model (CRM). Applying these methodologies to one specific MDB, the Inter-American Development Bank (IDB), the paper shows that S&P's approach is highly conservative in its evaluation of single name concentration risk and makes insufficient allowance for PCS. Calibrating the CRM with risk-neutral distributions, the paper examines the effect of PCS on MDB funding rates and compares model-implied funding spreads with those observed in the market.
hdl:11319/7686
Keywords: G11; G12; G24; 330; Multilateral development banks; Preferred creditor status; Credit ratings; Rating agencies